POTENSI PENCEMAR DAN KUALITAS MATA AIR PENIDA DAN GUYANGAN SEBAGAI SUMBER BAKU AIR MINUM DI NUSA PENIDA - Nyoman Sudipa; Ni Putu Suda Nurjani (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2022)
Water is an essential requirement for human life. Maintain water availability, both in terms of quality and quantity, in relation to the surrounding environmental conditions. The socio-cultural conditions of the people of Nusa Penida are very much influenced by the presence of water, even social conflicts occur because of the water crisis. The main problem with drinking water raw sources is the availability of water sources which continues to decline from year to year, while water demand continues to increase due to population growth. Areas that have limited water resources will cause economic resources to be used to meet water needs. As an area that has limited water resources, Nusa Penida has springs that are mostly difficult to reach and access by the community. Two springs with quite large discharge are Penida Spring and Guyangan Spring which have been distributed to the community and to fulfill tourism needs. This study aims to determine the feasibility of Penida and Guyangan Springs as a source of drinking water based on Governor of Bali Regulation Number 16 of 2016 concerning Environmental Quality Standards and Standard Criteria for Environmental Damage and to determine the potential sources of pollutants for these two springs. This study uses a quantitative approach combined with primary data sources from direct observations in the field and uses secondary data sources from literature and previous research. The results showed that the Penida and Guyangan Springs were in good condition and met quality standards. Potential sources of pollutants from Penida Springs come from residential activities and tourism activities, while Guyangan Springs does not have pollutants because they are located in a place that is difficult to reach and is in the bowels of Nusa Penida Island. Keywords: springs, standards, quality, pollutants, Nusa Penida